Experimental validation of in silico model‐predicted isocitrate dehydrogenase and phosphomannose isomerase from Dehalococcoides mccartyi. Issue 1 (16th September 2015) - Islam, M. Ahsanul; Tchigvintsev, Anatoli; Yim, Veronica; Savchenko, Alexei; Yakunin, Alexander F.; Mahadevan, Radhakrishnan; Edwards, Elizabeth A.
Summary: Gene sequences annotated as proteins of unknown or non‐specific function and hypothetical proteins account for a large fraction of most genomes. In the strictly anaerobic and organohalide respiring D ehalococcoides mccartyi, this lack of annotation plagues almost half the genome. Using a combination of bioinformatics analyses and genome‐wide metabolic modelling, new or more specific annotations were proposed for about 80 of these poorly annotated genes in previous investigations of D . mccartyi metabolism. Herein, we report the experimental validation of the proposed reannotations for two such genes (KB1_0495 and KB1_0553) from D . mccartyi strains in the KB‐1 community. KB1_0495 or Dm IDH was originally annotated as an NAD + ‐dependent isocitrate dehydrogenase, but biochemical assays revealed its activity primarily with NADP + as a cofactor. KB1_0553, also denoted as Dm PMI, was originally annotated as a hypothetical protein/sugar isomerase domain protein. We previously proposed that it was a bifunctional phosphoglucose isomerase/phosphomannose isomerase, but only phosphomannose isomerase activity was identified and confirmed experimentally. Further bioinformatics analyses of these two protein sequences suggest their affiliation to potentially novel enzyme families within their respective larger enzyme super families. Abstract : This work describes the model‐based identification and biochemical characterization of Phosphomannose isomerase and Isocitrate dehydrogenase from Dehalococcoides mccartyi